Science Education and Mobile Learning: A Content Analysis Review of the Web of Science Database - Odabasi, Metin; Uzunboylu, Huseyin; Popova, Olga V.; Kosarenko, Nikolay N.; Ishmuradova, Izida I. (Kassel Univ Press Gmbh, 2019)
The use of mobile technologies in education has appealed considerable interest and attention from educators and researchers in the last decade. Nonetheless, the effects of mobile learning on students' learning outcome in science education are still ambiguous. The time and place flexibility, ubiquity and easy accessibility of mobile devices are among the features that make them valuable in m-learning, especially in science education, at present times. Despite the large number of researches conducted, no bibliometrics study has been carried out in this topic so far. The aim of this review is to assess the progress of international publications in the area of science education and mobile learning. This content analysis review shows the trends in publications regarding mobile learning and science education researches indexed in Web of Science database between years 2004-2019. Out of 57 documents related to the topic of interest found in the database of Web of Science, the results demonstrate that the publication frequency has increased after 2012 where the most productive year was 2016. Most of the published documents were proceedings papers and original articles. Taiwan and United States are the countries with most work published where Pakistan, Taiwan and China are the countries that funded the most scientific research. The top journal involving the publications associated with this topic is Computers & Education journal. A more comprehensive criteria has been used in this content analysis which has interpreted in detail. This study can provide a much clear picture of the field to researchers, educational leaders and funders to incorporate new understandings into their research.
Keywords: Science education; mobile learning; content analysis; educational technology